Incorporation of biocides in nanocapsules for protective coatings used in maritime applications - Maia, F.
This work reports the synthesis and characterization of silica nanocapsules with biologically-active compounds 2-mercaptobenzothiazole and 4,5-dichloro-2-octyl-4-isothiazolin-3-one. The resulting particles were characterized by scanning electron microscopy, thermogravimetry and adsorption-desorption isotherms of N-2. The antibacterial activity was assessed for both nanocapsules dispersed in solution as well as incorporated in coating systems, using a recombinant bioluminescent Escherichia coli expressing the luxCDABE genes from the marine bioluminescent bacterium Aliivibrio fischeri. The decrease in light emission of the bacterial model, indicative as decrease of metabolic activity, was directly correlated with the level of biocide detected in solution by UV-Visible spectrophotometry. The results show that the developed nanomaterials show great potential for application in antifouling coatings. (C) 2015 Elsevier B.V. All rights reserved.